Copolyester films, laminated films and methods of using the same
By adjusting the dicarboxylic acid and alcohol components in the copolyester film, ensuring that the difference between the cold crystallization temperature and the glass transition temperature is greater than 60℃, the existing polyester films are solved inadequate elongation and heat resistance at room temperature. Problem, a copolyester film with high flexibility and heat resistance is achieved, which is suitable for high stretch processing of laminated structures.
Patent Information
- Application Number
- CN202080094687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2020-10-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-10-12
AI Technical Summary
The existing polyester films are insufficiently elongated and lack heat resistance at room temperature, making it difficult to meet the high tensile processing requirements of substrate films in laminated state, especially when manufacturing flexible displays and electronic components, they require both flexibility and Heat resistance.
The copolymerized polyester film containing terephthalic acid and dicarboxylic acid components with 4 to 10 carbon atoms is used, and the difference between the cold crystallization temperature and the glass transition temperature is more than 60°C, and the dicarboxylic acid is adjusted in the copolymerized polyester layer. The ratio of acid and alcohol components ensures that the tensile elongation of break of 25°C reaches more than 295% and the energy storage modulus of 120°C is more than 10MPa.
A copolymer polyester film with high flexibility and elongation at room temperature is realized, and at the same time it has moderate heat resistance. It is suitable for stretching and processing on the substrate film through a laminated structure to produce a film functional sheet with excellent performance.
Smart Images

Figure BDA0003765609880000421
Abstract
Description
Technical Field
[0001] The present invention relates to a copolyester film having a copolyester layer containing a copolyester, a laminated film having the copolyester film, and methods of using the same. Background Art
[0002] Polyester films are typically polyethylene terephthalate (PET) films, particularly biaxially stretched PET films, which are excellent in transparency, mechanical strength, heat resistance, flexibility, etc. and are therefore used in various fields such as industrial materials, optical materials, electronic component materials, and battery packaging materials.
[0003] Regarding this polyester film, for example, in Patent Document 1, as a softened polyester film that exhibits softness that conventional polyester films do not have and has excellent formability at relatively low temperatures and relatively low pressures, a softened polyester film is proposed, characterized in that the elastic modulus E' of the film is 20 MPa or less at 120° C. and 5 MPa or less at 180° C., the film haze is 1.0% or less, and as a diol constituent, it contains 29 to 32 mol % of 1,4-cyclohexanedimethanol units, and as a dicarboxylic acid constituent, it contains no isophthalic acid units.
[0004] In recent years, as image display devices, computers reduced in size to be portable (wearable computers) have attracted attention due to miniaturization and improved performance of portable terminals.
[0005] Ideally, the electronic device (wearable terminal) used in the wearable computer is present in a personal item such as a card, a bag, a watch, clothes, or shoes (Patent Document 2).
[0006] In addition, as the next generation of image display devices, flexible displays that can be bent freely are attracting attention. Flexible displays mainly use organic electroluminescent (organic EL) displays.
[0007] Since flexible displays use thin glass substrates or plastic substrates, the polyester films used in these image display device components are required to have not only the optical properties and durability required for conventional flat display panels, but also flexibility such that they do not break even when subjected to bending tests.
[0008] Furthermore, as one of the extended uses of soft polyester film, multilayer films with various functions obtained by using the so-called lamination stretching technology in which different materials are laminated and stretched have attracted attention (Non-Patent Document 1).
[0009] For example, as a combination of different materials, EVA resin-PVC, EVA-polyester, EVA-low density polyethylene, PVA-PVC, PVA-polyester, PVA-low density polyethylene, etc. can be illustrated. As for the functions to be given, gas barrier properties, heat sealability, scratch resistance, printability, moisture resistance, etc. can also be illustrated.
[0010] In addition, in recent years, the following situation has occurred: With the high performance of electronic devices such as smart phones, such as communication devices, and notebook personal computers, the electronic components carried therein also need to be miniaturized / higher performance. For example, when focusing on ceramic laminated capacitors, the thickness of the green sheets used tends to be further thinned, and it is necessary to stably manufacture thin film green sheets of about 0.5μm to 1μm. In the previous coating method, the sheet is generally formed by applying a low-viscosity slurry diluted with a solvent on a substrate film and drying it.
[0011] However, when a low-concentration slurry is used for coating and drying, the obtained green sheet may have pinholes, etc., and may not necessarily be sufficient in terms of performance. Therefore, as another method, as described in Patent Document 3, it is proposed that in the process of coating the slurry on a base film and drying, the base film and the slurry coating layer are stretched together to obtain a green sheet.
[0012] When different materials (eg, materials constituting slurry) as described above are laminated on a base film and stretched in a laminated state, there is an advantage that the occurrence of pinholes can be reduced by adjusting the slurry concentration (eg, increasing the concentration).
[0013] Furthermore, in addition to the use in manufacturing green sheets, studies have been conducted on laminating different materials such as resin layers on a base film to form a multilayer body, and stretching the multilayer body to stretch the resin layer provided on the base film.
[0014] Prior art literature
[0015] Patent Literature
[0016] Patent Document 1: Japanese Patent Application Publication No. 2014-169371
[0017] Patent Document 2: Japanese Patent Application Publication No. 2002-174688
[0018] Patent Document 3: Japanese Patent Application Laid-Open No. 10-250014
[0019] Non-patent literature
[0020] Non-patent document 1: "Fiber and Industry" Biaxial stretching technology of multilayer film ("Fiber and Industry" Biaxial stretching technology of multilayer film) by Mutsuo Kuga, (Vol.35, No.7 (1979)) Summary of the invention
[0021] Problem that the invention aims to solve
[0022] However, the stretching process in the state where different materials are stacked on the base film is in the following situation: the mechanical properties of the base film or the different materials provided on the base film, especially the elongation, are limited in processing conditions. For example, in the state where different materials are stacked before the stretching process, when the thickness of the different material layer is thick to obtain a different material sheet of the film by stretching, the base film is required to be able to be stretched at a high stretching ratio. The polyester film commonly used, such as the copolyester film using isophthalic acid, sometimes has insufficient elongation at room temperature and is difficult to stretch.
[0023] Furthermore, when focusing on materials that can be used as substrate films and that can be expected to have high elongation at room temperature, nylon, PVC, and PP (polypropylene) films can be exemplified. However, these films often have high elongation but lack heat resistance. For example, after a heat treatment process, the shrinkage rate of the film increases, making it difficult to use in applications that require dimensional accuracy.
[0024] Therefore, an object of the present invention is to provide a copolyester film having excellent flexibility and being able to achieve both contradictory properties of having high elongation at room temperature and good heat resistance.
[0025] Furthermore, a further limited object of the present invention is to provide a copolyester film suitable for producing a thin functional sheet by stretching a functional layer laminated on a base film, a laminated film, and a method of using the same.
[0026] Solutions for solving problems
[0027] The present invention takes the following contents as its gist.
[0028] [1] A copolyester film comprising a copolyester layer (A1) containing a copolyester (a1),
[0029] The copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and an alcohol component (Y2) other than ethylene glycol (Y1).
[0030] The difference (ΔTcg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of the copolyester film exceeds 60°C.
[0031] [2] A copolyester film comprising a copolyester layer (A1) containing a copolyester (a1),
[0032] The copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X), and an alcohol component (Y2) other than ethylene glycol (Y1), and contains two or more of the other alcohol components (Y2).
[0033] The difference (ΔTcg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of the copolyester film exceeds 60°C.
[0034] [3] The copolyester film according to [1] or [2] above, wherein the proportion of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms in the total polyester (A) contained in the copolyester layer (A1) is 3 to 50 mol%.
[0035] [4] The copolyester film according to any one of [1] to [3] above, wherein the ratio of the other alcohol component (Y2) in the total polyester (A) contained in the copolyester layer (A1) to the alcohol components is 15 to 60 mol%.
[0036] [5] The copolyester film according to any one of [1] to [4] above, wherein the tensile elongation at break at 25°C is 295% or more.
[0037] [6] The copolyester film according to any one of [1] to [5] above, wherein the storage modulus at 25°C is 2500 MPa or less and the storage modulus at 120°C is 10 MPa or more.
[0038] [7] The copolyester film according to any one of [1] and [3] to [6] above, wherein the dicarboxylic acid component (X2) having 4 to 10 carbon atoms contains an aliphatic dicarboxylic acid.
[0039] [8] The copolyester film according to [7] above, wherein the aliphatic dicarboxylic acid contains adipic acid.
[0040] [9] The copolyester film according to any one of [1] to [8] above, wherein the other alcohol component (Y2) contains 1,4-butanediol.
[0041]
[10] The copolyester film according to any one of [1] to [9] above, wherein the other alcohol component (Y2) contains 1,4-butanediol and 1,6-hexanediol.
[0042]
[11] The copolyester film according to any one of [1] to
[10] above, wherein the copolyester layer (A1) further comprises a polyester (a2),
[0043] The polyester (a2) is a polyester other than the copolyester (a1), and contains terephthalic acid as a dicarboxylic acid component and ethylene glycol as an alcohol component.
[0044]
[12] The copolyester film according to any one of [1] to
[11] , wherein the copolyester layer (A1) comprises a polyester layer (B1) and a polyester layer (B2) on both the front and back sides thereof.
[0045]
[13] A laminated film comprising the copolyester film as described in any one of [1] to
[12] above and a functional layer provided on at least one surface of the copolyester film.
[0046]
[14] The laminated film according to
[13] above, wherein the functional layer is a resin layer comprising a resin containing a vinyl alcohol structural unit.
[0047]
[15] The laminated film according to
[13] or
[14] above, wherein the functional layer constitutes a green sheet.
[0048]
[16] The laminated film according to
[13] or
[14] above, wherein the functional layer constitutes a polarizer.
[0049]
[17] The laminated film according to
[13] above, wherein the functional layer is an adhesive layer.
[0050]
[18] The laminated film according to
[17] above, wherein the adhesive layer contains a conductive material.
[0051]
[19] The laminated film according to
[13] above, wherein the functional layer is a conductive layer.
[0052]
[20] A method for using a copolyester film or a laminate film, comprising the step of stretching the copolyester film described in any one of [1] to
[12] or the laminate film described in any one of
[13] to
[19] above.
[0053]
[21] The method for using the copolyester film or laminated film according to
[20] above, wherein the stretching is performed in air or in water.
[0054]
[22] The method for using the copolyester film or laminated film according to
[20] or
[21] above, wherein the stretching is performed at a stretching ratio of 2.0 to 6.0 times.
[0055]
[23] The copolyester film according to any one of [1] to
[12] , which is used for any of an adhesive tape, a surface protection film, and a dicing tape for a semiconductor.
[0056]
[24] The laminated film according to any one of
[13] to
[19] above, which is used for any of an adhesive tape, a surface protection film, and a dicing tape for a semiconductor.
[0057]
[25] The method of use according to
[20] or
[21] , wherein the copolyester film or laminated film is used for any of an adhesive tape, a surface protection film and a dicing tape for a semiconductor.
[0058]
[25] The copolyester film according to any one of [1] to
[12] above, which is used for any of a wearable terminal, a bioelectrode substrate, and a biosensor substrate.
[0059]
[26] The laminated film according to any one of
[13] to
[19] above, which is used for any of a wearable terminal, a bioelectrode substrate, and a biosensor substrate.
[0060]
[27] The method of use according to
[20] or
[21] , wherein the copolyester film or laminated film is used for any of a wearable terminal, a bioelectrode substrate, and a biosensor substrate.
[0061]
[28] The copolyester film according to any one of [1] to
[12] above, which is used for producing electronic components.
[0062]
[29] The laminated film according to any one of
[13] to
[19] above, which is used for producing electronic components.
[0063]
[30] The method of use according to
[20] or
[21] above, wherein the copolyester film or laminated film is used for the production of electronic components.
[0064]
[31] The copolyester film according to any one of [1] to
[12] above, which is used for producing an optical component.
[0065]
[32] The laminated film according to any one of
[13] to
[19] above, which is used for producing an optical component.
[0066]
[33] The method of use according to
[20] or
[21] above, wherein the copolyester film or laminated film is used for the production of optical components.
[0067] Effects of the Invention
[0068] The copolyester film of the present invention has excellent flexibility at room temperature, and is not only soft but also has a large elongation and, as an opposite characteristic, a moderately low heat shrinkage characteristic, and can have sufficient heat resistance for practical use.
[0069] Furthermore, according to the present invention, for example, a copolyester film suitable for producing a thin functional sheet by stretching a functional layer laminated on a base film, a laminated film, and a method of using the same can be provided. DETAILED DESCRIPTION
[0070] Next, an example of an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.
[0071] <The present copolyester film>
[0072] The copolyester film according to one embodiment of the present invention (referred to as "the present copolyester film") is a single-layer film or a laminated film comprising a copolyester layer (A1) containing the copolyester (a1).
[0073] The copolyester film is preferably a stretched film stretched in a uniaxial direction or a biaxial direction, and may be a uniaxially stretched film or a biaxially stretched film. Among them, a biaxially stretched film is preferred from the viewpoint of excellent balance of mechanical properties and flatness.
[0074] When the copolyester film is such a stretched film, it is easy to make the storage modulus at 120°C to be 10 MPa or more, or the tensile elongation at break at 25°C to be 295% or more.
[0075] <Copolyester layer (A1)>
[0076] The copolyester layer (A1) is a layer containing the copolyester (a1). The copolyester layer (A1) preferably contains polyester (a2) in addition to the copolyester (a1). In addition to the copolyester (a1) and polyester (a2), the copolyester layer (A1) may also contain resin (a3).
[0077] (Copolyester (a1))
[0078] In one embodiment of the present invention, the copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and an alcohol component (Y2) other than ethylene glycol (Y1). The copolyester (a1) may be crystalline or amorphous.
[0079] The dicarboxylic acid component (X2) having 4 to 10 carbon atoms refers to a dicarboxylic acid component having 4 to 10 carbon atoms other than terephthalic acid (X1).
[0080] The copolyester (a1) in this embodiment is a polycondensate of a dicarboxylic acid containing terephthalic acid (X1) and a dicarboxylic acid component (X2) having 4 to 10 carbon atoms and an alcohol component containing an alcohol component (Y2) other than ethylene glycol (Y1). The alcohol component is usually a diol component.
[0081] In the present invention, by using a dicarboxylic acid component having 4 to 10 carbon atoms as the dicarboxylic acid, it is easy to ensure flexibility, elongation, etc. at low temperatures.
[0082] As the dicarboxylic acid component (X2) having 4 to 10 carbon atoms, aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, polyfunctional acids, etc. can be cited. Among these, aliphatic dicarboxylic acids are preferred from the viewpoint of improving the storage modulus at room temperature and improving the flexibility and elongation. Aliphatic dicarboxylic acids can be used alone as the dicarboxylic acid component (X2) having 4 to 10 carbon atoms, or in combination with other dicarboxylic acid components having 4 to 10 carbon atoms.
[0083] As the aliphatic dicarboxylic acid having 4 to 10 carbon atoms, there can be mentioned saturated aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. Among them, from the viewpoint of the ease of reaction during polymerization, adipic acid and sebacic acid are more preferred, and adipic acid is further preferred. In addition, as the aromatic dicarboxylic acid, there can be mentioned isophthalic acid, etc.
[0084] In one embodiment, the proportion of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms in the dicarboxylic acid components constituting the copolyester (a1) can be adjusted in such a way that the proportion of (X2) in the entire polyester (A) described later is within a prescribed range, and is not particularly limited, for example, 5 to 35 mol%, preferably 8 to 25 mol%, and more preferably 10 to 20 mol%.
[0085] In one embodiment, the proportion of terephthalic acid (X1) in the dicarboxylic acid component constituting the copolyester (a1) is, for example, 65 to 95 mol %, preferably 75 to 92 mol %, and more preferably 80 to 90 mol %.
[0086] In one embodiment of the copolyester (a1), the dicarboxylic acid component may be composed of terephthalic acid (X1) and a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and may contain a dicarboxylic acid component (other dicarboxylic acid component (X3)) other than terephthalic acid (X1) and a dicarboxylic acid component (X2) having 4 to 10 carbon atoms as a copolymer component within the scope not impairing the gist of the present invention. Examples of such dicarboxylic acid components include dodecanedioic acid, eicosanoic acid, dimer acid, and derivatives thereof.
[0087] In the above embodiment, the ratio of the other dicarboxylic acid component (X3) in the dicarboxylic acid component constituting the copolyester (a1) is, for example, 10 mol% or less, preferably 5 mol% or less, more preferably 3 mol% or less, and most preferably 0 mol%.
[0088] Examples of other alcohol components (Y2) include aliphatic diols such as 1,4-butanediol, 1,4-hexanediol, 1,6-hexanediol, diethylene glycol, trimethylene glycol, pentamethylene glycol, octamethylene glycol, decamethylene glycol, neopentyl glycol, and 2-ethyl-2-butyl-1,3-propanediol; and 1,2-cyclohexanediol, 1,1-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,5-norborneol. Alicyclic diols such as alkanediol; aromatic diols such as o-phthalimethanol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, bis(4-β-hydroxyethoxyphenyl)sulfonic acid; ethylene oxide adducts or propylene oxide adducts of 2,2-bis(4'-hydroxyphenyl)propane, dimer diol, etc. These may be contained alone or in combination of two or more.
[0089] Among the above, aliphatic diols are preferred from the viewpoint of flexibility and crystallinity. The aliphatic diol is preferably an aliphatic diol having 4 to 8 carbon atoms, and more preferably an aliphatic diol having 4 to 6 carbon atoms.
[0090] More specifically, the aliphatic diol is preferably at least one selected from diethylene glycol, 1,4-butanediol, 1,4-hexanediol and 1,6-hexanediol. In addition, the other alcohol component (Y2) more preferably contains at least 1,4-butanediol. In addition, the alcohol component (Y2) is preferably used in two or more kinds. When using two or more kinds, it can be appropriately selected from the above substances. Among them, the alcohol component in the copolyester (a1) further preferably contains both 1,4-butanediol and 1,6-hexanediol. By using two or more other alcohol components (Y2), it is easier to adjust the crystallinity in combination with the acid component than before.
[0091] In addition, the copolyester (a1) may contain ethylene glycol (Y1) as an alcohol component (copolymer component). It should be noted that any of the polyesters (A) constituting the copolyester layer (A1) may contain ethylene glycol (Y1) as an alcohol component. Therefore, when the copolyester (a1) does not contain ethylene glycol (Y1) as an alcohol component (copolymer component), for example, the polyester (a2) may contain ethylene glycol (Y1) as an alcohol component (copolymer component).
[0092] The proportion of other alcohol components (Y2) in the alcohol components constituting the copolyester (a1) can be adjusted so that the proportion of (Y2) in the entire polyester (A) described later is within a prescribed range, for example, 50 to 100 mol%, preferably 70 to 100 mol%, and more preferably 90 to 100 mol%.
[0093] In addition, the copolyester (a1) contains a certain amount or more of a polyester having terephthalic acid, a dicarboxylic acid having 4 to 10 carbon atoms, and one or both of 1,4-butanediol and 1,6-hexanediol as a structural unit, so that the copolyester layer (A1) is soft, excellent in elongation at low temperatures, and has both strength and heat resistance.
[0094] In another embodiment of the present invention, the copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X), and an alcohol component (Y2) other than ethylene glycol (Y1), and contains two or more other alcohol components (Y2).
[0095] Therefore, the copolyester (a1) in another embodiment of the present invention is a polycondensate of a dicarboxylic acid containing terephthalic acid (X1) and a dicarboxylic acid component (X) and an alcohol component containing another alcohol component (Y2) other than ethylene glycol (Y1), and the other alcohol component (Y2) contains two or more alcohol components. It should be noted that the alcohol component is usually a diol component.
[0096] The dicarboxylic acid component (X) refers to a dicarboxylic acid component other than terephthalic acid (X1). In the present specification, "dicarboxylic acid" is a concept that also includes terephthalic acid (X1).
[0097] In addition, the other alcohol component (Y2) in other embodiments is as described above except that two or more kinds are used, and the details when two or more kinds are used are also as described above.
[0098] In the present invention, by using two or more alcohol components (Y2), it is easier to adjust the crystallinity in combination with the acid component than before, and it is also easier to adjust the difference between Tcc and Tg described later. In particular, in the present invention, a significant effect is achieved in combination with a dicarboxylic acid component (X2) having 4 to 10 carbon atoms. Therefore, in the present invention, in another embodiment, the dicarboxylic acid component (X) also preferably contains a dicarboxylic acid component (X1) having 4 to 10 carbon atoms. In this case, the details of the copolyester (a1) are as described in the copolyester (a1) of the above embodiment.
[0099] However, in another embodiment, the dicarboxylic acid used in the copolyester (a1) may consist of terephthalic acid (X1) and other dicarboxylic acid components (X3). In this case, the details of the other dicarboxylic acid component (X3) are as described above.
[0100] In each embodiment, the copolyester (a1) may be used alone or in combination of two or more.
[0101] (Intrinsic viscosity (IV) of copolyester (a1))
[0102] The intrinsic viscosity (IV) of the copolyester (a1) (when two or more copolyesters (a1) are used, calculated as a polyester mixture) is preferably 0.40 dL / g to 1.20 dL / g, more preferably 0.45 dL / g or more, further preferably 0.48 dL / g or more, and more preferably 1.15 dL / g or less, further preferably 1.10 dL / g or less.
[0103] When the intrinsic viscosity of the copolyester (a1) is within this range, the copolyester (a1) can be obtained with excellent molding processability without deteriorating productivity.
[0104] The intrinsic viscosity (IV) of the polyester is measured at 30° C. by precisely weighing 1 g of the polyester after removing the components insoluble in the polyester, dissolving the polyester in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (weight ratio).
[0105] In order to make the ratio of each component in the total polyester (A) described later fall within a prescribed range, the content of the copolyester (a1) only needs to be a certain proportion or more in the resin component constituting the copolyester layer (A1). The copolyester (a1) occupies, for example, 20% by mass or more, preferably 30% by mass or more, more preferably 35% by mass or more, and further preferably 50% by mass or more in the resin component constituting the copolyester layer (A1), and for example, it can occupy 80% by mass or more. In addition, the copolyester (a1) can occupy 100% by mass or less in the resin component constituting the copolyester layer (A1), for example, it can occupy 70% by mass or less, and it can also occupy 60% by mass or less.
[0106] (Polyester (a2))
[0107] In the copolyester layer (A1), the constituent resin may be only the copolyester (a1), but preferably contains the polyester (a2) in addition to the copolyester (a1).
[0108] Here, in each of the above embodiments, the polyester (a2) is a polyester other than the copolyester (a1) in each of the above embodiments, and is a homopolyester or copolyester containing terephthalic acid (X1) as a dicarboxylic acid component and ethylene glycol (Y1) as an alcohol component.
[0109] The above-mentioned homopolyester is polyethylene terephthalate in which the dicarboxylic acid component is terephthalic acid (X1) and the alcohol component is ethylene glycol (Y1). As polyester (a2), homopolyester is preferably used. Among them, when it is expressed as a homopolyester, the alcohol component may contain diethylene glycol that is inevitably mixed in. Specifically, in polyethylene terephthalate (homopolyester), the proportion of diethylene glycol in the alcohol component can be, for example, less than 5 mol%, and can also be less than 3 mol%. The same is also true in the polyester (B) described later.
[0110] In addition, when diethylene glycol is used as one of raw materials to produce (polycondense) polyester, a part of ethylene glycol is modified to become diethylene glycol, and is introduced into the polyester skeleton.
[0111] When the polyester (a2) is a copolyester, the copolyester may be, for example, a copolymer of a dicarboxylic acid component composed of terephthalic acid (X1) and a dicarboxylic acid component other than terephthalic acid (X1) and an alcohol component composed of ethylene glycol. In this case, the alcohol component may contain diethylene glycol inevitably mixed in as described above, and the content ratio of diethylene glycol in this case is as described above. It should be noted that, in this way, a copolymer polyester in which the alcohol component is composed of ethylene glycol and diethylene glycol inevitably mixed in is used as polyester (a2).
[0112] When the polyester (a2) is a copolyester, the copolyester may be, for example, a copolymer of terephthalic acid (X1) and an alcohol component including ethylene glycol and an alcohol component (Y2) other than ethylene glycol (Y1).
[0113] In the above-mentioned embodiments, if the polyester (a2) is a polyester other than the polyester (a1), it may be a polyester other than these.
[0114] When the polyester (a2) is a copolyester, as the dicarboxylic acid component other than terephthalic acid (X1), aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, polyfunctional acids, etc. can be listed. As these dicarboxylic acid components, the same substances as those listed in the copolyester (a1) can be listed. Here, the dicarboxylic acid component other than terephthalic acid (X1) can be used alone or in combination of two or more. It should be noted that as the dicarboxylic acid component other than terephthalic acid (X1), a dicarboxylic acid component having 4 to 10 carbon atoms can be used, and dicarboxylic acid components other than these such as dimer acid can also be used, and they can also be used in combination. As the dicarboxylic acid component, an aromatic dicarboxylic acid is preferred, among which isophthalic acid is more preferably included.
[0115] When the polyester (a2) is a copolyester and the dicarboxylic acid component contains a dicarboxylic acid component other than terephthalic acid, the proportion of the dicarboxylic acid component other than terephthalic acid in the dicarboxylic acid component is preferably 1 to 30 mol%, more preferably 3 mol% or more, and even more preferably 5 mol% or more, and more preferably 20 mol% or less, and even more preferably 15 mol% or less.
[0116] When the polyester (a2) is a copolyester, as the alcohol component (Y2) other than ethylene glycol (Y1), the compounds listed in the copolyester (a1) can be appropriately selected and used, and preferably 1,4-butanediol, 1,6-hexanediol, 1,4-hexanediol, diethylene glycol, trimethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, etc. are listed.
[0117] When the polyester (a2) is a copolymer polyester and the alcohol component contains an alcohol component (Y2) other than ethylene glycol (Y1), in the copolymer polyester, the proportion of the alcohol component (Y2) other than ethylene glycol in the alcohol component is preferably 1 mol% or more and less than 100 mol%, more preferably 3 mol% or more, further preferably 5 mol% or more, more preferably 90 mol% or less, further preferably 50 mol% or less, further preferably 30 mol% or less, and particularly preferably 10 mol% or less.
[0118] The intrinsic viscosity (IV) of the polyester (a2) (when two or more polyesters (a2) are used, calculated as a polyester mixture) is preferably 0.40 dL / g to 1.20 dL / g, more preferably 0.45 dL / g or more, further preferably 0.48 dL / g or more, and more preferably 1.15 dL / g or less, further preferably 1.10 dL / g or less.
[0119] When the intrinsic viscosity of the copolyester (a2) is within this range, the copolyester (a2) can be obtained with excellent molding processability without deteriorating productivity.
[0120] The polyester (a2) may be used alone or in combination of two or more.
[0121] Regarding the content of polyester (a2), as long as the ratio of each component in the polyester (A) is within the range described below, among the resin components constituting the copolyester layer (A1), it occupies, for example, 80% by mass or less, preferably 70% by mass or less, more preferably 65% by mass or less, and further preferably 50% by mass or less, and preferably 30% by mass or more, and more preferably 40% by mass or more.
[0122] (Resin (a3))
[0123] The copolyester layer (A1) may be a layer containing a resin (a3) other than the copolyester (a1) and the polyester (a2). As the resin (a3), any resin compatible with the copolyester (a1) may be used, and when the polyester (a2) is used, the resin may also be compatible with the polyester (a2).
[0124] If the copolyester layer (A1) is a layer having an island structure formed by copolyester (a1) and resin (a3) or copolyester (a1), polyester (a2) and resin (a3), then by selecting polyesters such as polyolefins, polystyrene, acrylic resins, urethane resins, polybutylene terephthalate (PBT) as resin (a3), it is possible to impart shielding properties and heat resistance.
[0125] In the copolyester layer (A1), the mass ratio of the total amount of the copolyester (a1) and the polyester (a2) to the resin (a3) ((a1+a2):a3) is preferably 98:2 to 50:50, more preferably 95:5 to 60:40, and more preferably 90:10 to 65:35.
[0126] In addition, the resin (a3) is preferably a resin compatible with the copolyester (a1) or with the copolyester (a1) and the polyester (a2), and is a resin having a melting point of 270° C. or less and a glass transition temperature of 30 to 120° C. By selecting such a resin (a3), the glass transition temperature of the copolyester layer (A1) can be increased, and the heat resistance can be improved. Examples of such resins include polybutylene terephthalate (PBT), but are not limited to PBT.
[0127] The resin (a3) may be used alone or in combination of two or more.
[0128] (Proportion of each ingredient)
[0129] In the present invention, the ratio of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms in the total polyester (A) contained in the copolyester layer (A1) is, for example, 3 to 50 mol%. It should be noted that the total polyester (A) mentioned here refers to the total polyester contained in the copolyester layer (A1). Therefore, the above ratio refers to the ratio based on the dicarboxylic acid component constituting the total polyester (A), and similar terms are used in the following with the same meaning.
[0130] Here, by setting the ratio of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms to 3 mol% or more, the effect of using the dicarboxylic acid component (X2) having 4 to 10 carbon atoms can be fully obtained, and the flexibility and elongation at low temperatures can be ensured. By setting it to 50 mol% or less, the heat shrinkage rate becomes low and heat resistance can be ensured.
[0131] From the viewpoint of achieving good flexibility and elongation at low temperatures and ensuring heat resistance, the proportion of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms is preferably 5 mol% or more, more preferably 7 mol% or more, and is preferably 45 mol% or less, more preferably 40 mol% or less, further preferably 25 mol% or less, and still more preferably 12 mol% or less.
[0132] As described above, adipic acid is preferably used as the dicarboxylic acid component (X2) having 4 to 10 carbon atoms. When adipic acid is used, adipic acid may be used alone as the dicarboxylic acid component (X2) having 4 to 10 carbon atoms, or a dicarboxylic acid having 4 to 10 carbon atoms other than adipic acid may be used in combination.
[0133] The proportion of adipic acid in the dicarboxylic acid components in the entire polyester (A) is, for example, 3 to 50 mol%, preferably 4 mol% or more, more preferably 5 mol% or more, further preferably 7 mol% or more, and is preferably 40 mol% or less, more preferably 25 mol% or less, further preferably 12 mol% or less, and further preferably 10 mol% or less.
[0134] From the viewpoint of maintaining various properties such as heat resistance well, the ratio of terephthalic acid (X1) in the dicarboxylic acid component in the entire polyester (A) is, for example, 50 to 97 mol%, preferably 95 mol% or less, more preferably 93 mol% or less, and preferably 60 mol% or more, more preferably 65 mol% or more, further preferably 75 mol% or more, and further preferably 88 mol% or more.
[0135] The ratio of other dicarboxylic acid (X3) in the dicarboxylic acid component in the entire polyester (A) is, for example, 10 mol% or less, preferably 5 mol% or less, more preferably 3 mol% or less, and most preferably 0 mol%. That is, it is most preferred that the dicarboxylic acid component in the polyester (A) does not contain other dicarboxylic acid (X3).
[0136] In addition, the dicarboxylic acid component of the polyester (A) contained in the copolyester layer (A1) can be quantitatively determined by measuring the 1H-NMR spectrum.
[0137] In the present invention, the proportion of other alcohol components (Y2) in the total polyester (A) contained in the copolyester layer (A1) in the alcohol components is, for example, 15 to 60 mol%. If it is 15 mol% or more, it is easy to ensure flexibility and elongation at low temperatures. In addition, if it is 60 mol% or less, the thermal shrinkage rate becomes low and it is easy to ensure heat resistance. From the viewpoint of making the flexibility and elongation at low temperatures good and ensuring heat resistance, the proportion of other alcohol components (Y2) is preferably 20 mol% or more, more preferably 25 mol% or more, further preferably 30 mol% or more, and preferably 55 mol% or less.
[0138] From the viewpoint of ensuring flexibility and high elongation at low temperatures, the other alcohol component (Y2) preferably contains at least 1,4-butanediol, and as mentioned above, it is preferred to use two or more. Among them, it is particularly preferred to contain both 1,4-butanediol and 1,6-hexanediol. By using two or more other alcohol components (Y2), it has the advantage of being easier to adjust the crystallinity in combination with the acid component than before. In particular, it has a significant effect in the combination of the present application with the dicarboxylic acid component (X2) having 4 to 10 carbon atoms.
[0139] The proportion of 1,4-butanediol and 1,6-hexanediol in the alcohol components in the entire polyester (A) is preferably 15 to 60 mol%, more preferably 20 mol% or more, further preferably 25 mol% or more, further preferably 30 mol% or more, and more preferably 55 mol% or less.
[0140] The ratios of 1,4-butanediol and 1,6-hexanediol refer to the ratio of 1,4-butanediol when only 1,4-butanediol is used, the ratio of 1,4-hexanediol when only 1,6-hexanediol is used, and the total ratio of 1,4-butanediol and 1,6-hexanediol when both are used.
[0141] When 1,4-butanediol and 1,6-hexanediol are contained, the ratio of the molar amount of 1,6-hexanediol to the molar amount of 1,4-butanediol is, for example, 0.5 or more, preferably 0.7 or more, more preferably 0.8 or more, and further preferably 0.9 or more, or, for example, 2.5 or less, preferably 2.0 or less, more preferably 1.6 or less, and further preferably 1.4 or less.
[0142] The proportion of ethylene glycol (Y1) in the alcohol component in the entire polyester (A) is, for example, 40 to 85 mol%, preferably 45 mol% or more, preferably 80 mol% or less, more preferably 75 mol% or less, and further preferably 70 mol% or less.
[0143] In addition, each alcohol component of the polyester (A) contained in the copolyester layer (A1) can be quantitatively determined by measuring the 1H-NMR spectrum.
[0144] As a particularly preferred embodiment among the above, the following embodiment can be cited: the copolyester (a1) is a crystalline copolyester (Aa) formed by a copolymer of terephthalic acid and an aliphatic dicarboxylic acid having 4 to 10 carbon atoms and one or both of 1,4-butanediol and 1,6-hexanediol, wherein the proportion of the aliphatic dicarboxylic acid having 4 to 10 carbon atoms in the entire polyester (A) in the dicarboxylic acid component is 3 to 50 mol%, and the total proportion of 1,4-butanediol and 1,6-hexanediol in the alcohol component is 15 to 60 mol%.
[0145] Generally, when the ratio of copolymer components is increased in order to reduce the elastic modulus, the crystallinity of the copolyester decreases and becomes amorphous. Although the copolyester (Aa) can achieve a low elastic modulus due to the high ratio of the copolymer components, it still maintains crystallinity and can be thermally fixed by heat treatment after stretching. As a result, the copolyester (Aa) is soft and has good elongation and strength, and can also suppress thermal shrinkage.
[0146] The copolyester film containing the copolyester (a1) or the copolyester (a1) and the polyester (a2) also has good solvent resistance. Therefore, when the resin layer is formed using an organic solvent, the copolyester film can be prevented from being dissolved by the solvent as described later.
[0147] (Polyester blend)
[0148] As described above, the polyester (A) contained in the copolyester layer (A1) may be one polyester or a blend of two or more polyesters. When the polyester (A) is composed of one polyester, that is, when the copolyester layer (A1) contains one polyester as the copolyester (a1), the polyester is preferably a copolyester (a1) containing a dicarboxylic acid having 4 to 10 carbon atoms and terephthalic acid as the dicarboxylic acid component, and containing ethylene glycol and one or both of 1,4-butanediol and 1,6-hexanediol as the alcohol component.
[0149] On the other hand, when the polyester (A) contained in the copolyester layer (A1) is composed of two or more polyesters, that is, when the copolyester layer (A1) contains a polyester blend composed of two or more polyesters as the polyester (A), the polyester blend preferably contains a dicarboxylic acid having 4 to 10 carbon atoms and terephthalic acid as the aforementioned dicarboxylic acid components, and contains ethylene glycol and one or both of 1,4-butanediol and 1,6-hexanediol as the aforementioned diol components.
[0150] In this case, the polyester blend only needs to have the above structural units. For example, when the polyester blend is a mixed resin of a first polyester and a second polyester, each of the first polyester and the second polyester does not necessarily have all of the above structural units.
[0151] In the copolyester layer (A1), the polyester (A) is the main component resin. The "main component resin" refers to the resin that is contained in the largest proportion among the resin components constituting the copolyester layer (A).
[0152] The content of the polyester (A) is, for example, 50 mass % or more, preferably 60 mass % or more, more preferably 80 mass % or more, and is not particularly limited as long as it is 100 mass % or less, based on the resin component contained in the copolyester layer (A1).
[0153] In addition, the content of polyester (A) means the total amount of all polyesters contained in the copolyester layer (A1).
[0154] The copolyester layer (A1) may contain particles. Specific examples of the particles include inorganic particles such as silicon dioxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. Furthermore, in the polyester production process, precipitated particles obtained by precipitating or microdispersing a part of a metal compound such as a catalyst may also be used.
[0155] The particles may be used alone or in combination of two or more.
[0156] The shape of the particles used is not particularly limited, and any of spherical, blocky, rod-shaped, flat, etc. can be used. In addition, the hardness, specific gravity, color, etc. are not particularly limited. These series of particles can be used in combination of two or more as needed.
[0157] The average particle size of the particles used is preferably 5 μm or less, more preferably 0.1 to 4 μm. By using particles having an average particle size within the above range, appropriate surface roughness can be imparted to the film, and good sliding properties and smoothness can be ensured.
[0158] It should be noted that the average particle size of the particles can be obtained by arbitrarily selecting 10 or more particles present in the copolyester layer (A1) using a scanning electron microscope (SEM), measuring the diameter of each particle, and obtaining the average value thereof. In the case of non-spherical particles, the average value of the longest diameter and the shortest diameter ((short diameter + long diameter) / 2) can be measured as the diameter of each particle.
[0159] The copolyester layer (A1) may contain two or more types of particles having different particle diameters in combination.
[0160] The particle content in the copolyester layer (A1) is preferably 5% by mass or less, more preferably in the range of 0.0003 to 3% by mass, and further preferably in the range of 0.001 to 0.2% by mass. By setting the particle content within the above range, it is easy to ensure the transparency of the substrate film and impart slippage to the substrate film. In addition, by suppressing the particle content to a low level, it is easy to increase the tensile elongation at break.
[0161] The copolyester layer (A1) may contain, in addition to the above-mentioned particles, at least one additive selected from a crystal nucleating agent, an antioxidant, an anti-coloring agent, a pigment, a dye, an ultraviolet absorber, a release agent, a lubricant, a flame retardant, an antistatic agent, etc. as required.
[0162] (Method for producing copolyester (a1))
[0163] The method for producing the copolyester (a1) is not particularly limited, and a common method can be applied. For example, first, a dicarboxylic acid component containing terephthalic acid or its ester-forming derivative and a dicarboxylic acid or its ester-forming derivative other than terephthalic acid such as a dicarboxylic acid having 4 to 10 carbon atoms and an alcohol component containing an alcohol component other than ethylene glycol are mixed in a predetermined ratio under stirring to prepare a raw material slurry (raw material slurry preparation step). Next, the raw material slurry is heated under normal pressure or pressure to cause an esterification reaction to produce a polyester oligomer (hereinafter sometimes referred to as "oligomer") (oligomer preparation step). Thereafter, a dicarboxylic acid or its ester-forming derivative other than terephthalic acid such as a dicarboxylic acid having 4 to 10 carbon atoms and the above-mentioned alcohol component are further added to the obtained oligomer, and the pressure is gradually reduced in the presence of an ester exchange catalyst, while heating, so that it undergoes a melt polycondensation reaction to obtain a polyester (polyester preparation step). The obtained polyester can be further subjected to a solid phase polycondensation reaction (solid phase polycondensation step) as required.
[0164] The method for producing the polyester (a1) is not limited to the above method, and the dicarboxylic acid other than terephthalic acid or its ester-forming derivatives such as dicarboxylic acids having 4 to 10 carbon atoms need not be added to both the raw material slurry and the oligomer, and may be added only to the raw material slurry or only to the oligomer. In addition, terephthalic acid or its ester-forming derivatives may be added only to the raw material slurry or to the oligomer.
[0165] Similarly, the alcohol component may be added to both the raw material slurry and the oligomer, or may be added only to the raw material slurry.
[0166] Examples of the transesterification catalyst include antimony compounds such as antimony trioxide; germanium compounds such as germanium dioxide and germanium tetroxide; titanium compounds such as titanium alkoxides such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate; tin compounds such as dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethylditin oxide, cyclohexylditin oxide, didodecyltin oxide, triethylhydridotin oxide, triphenyltin hydroxide, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, methylstannic acid, ethylstannic acid, and butylstannic acid; magnesium compounds such as magnesium acetate, magnesium hydroxide, magnesium carbonate, magnesium oxide, magnesium alkoxide, and magnesium hydrogen phosphate; and calcium compounds such as calcium acetate, calcium hydroxide, calcium carbonate, calcium oxide, calcium alkoxide, and calcium hydrogen phosphate.
[0167] In addition, these catalysts may be used alone or in combination of two or more.
[0168] In addition, when producing polyester, it is preferred to use a stabilizer in combination with the transesterification catalyst. Examples of the stabilizer include orthophosphoric acid, polyphosphoric acid, and pentavalent phosphorus compounds such as trimethyl phosphate, triethyl phosphate, tri-n-butyl phosphate, trioctyl phosphate, triphenyl phosphate, tricresyl phosphate, tri(triethylene glycol) phosphate, ethyl diethyl phosphoacetate, methyl acid phosphate, ethyl acid phosphate, isopropyl acid phosphate, butyl acid phosphate, monobutyl phosphate, dibutyl phosphate, dioctyl phosphate, and triethylene glycol acid phosphate; and trivalent phosphorus compounds such as phosphorous acid, hypophosphorous acid, diethyl phosphite, tridodecyl phosphite, trinonyldecyl phosphite, and triphenyl phosphite.
[0169] Among them, trivalent phosphorus compounds generally have stronger reducing properties than pentavalent phosphorus compounds, and there is a concern that the metal compound added as a polycondensation catalyst may be reduced and precipitated, thereby causing the generation of foreign matter. Therefore, pentavalent phosphorus compounds are preferred.
[0170] The reaction pressure in the melt polycondensation reaction is preferably 0.001 kPa to 1.33 kPa in absolute pressure. The reaction temperature in the melt polycondensation reaction is preferably 220°C to 280°C, and more preferably 230°C to 260°C.
[0171] The solid phase polycondensation reaction can be performed under reduced pressure or in an inert gas atmosphere, and the reaction temperature is preferably 180° C. to 220° C. The reaction time of the solid phase polycondensation reaction is preferably 5 hours to 100 hours.
[0172] By adopting the above-mentioned melt polycondensation reaction conditions and solid phase polycondensation reaction conditions, a polyester having a desired intrinsic viscosity can be obtained.
[0173] <Multi-layer structure>
[0174] As described above, the copolyester film may have a multilayer structure including the copolyester layer (A1) and other layers.
[0175] When the copolyester film has a multilayer structure, for example, it may have a copolyester layer (A1), and a polyester layer (B1) and a polyester layer (B2) laminated on both sides of the copolyester layer (A1). Each of the polyester layer (B1) and the polyester layer (B2) contains the polyester (B) as the main component resin.
[0176] Here, the "main component resin" refers to the resin that is contained in the largest proportion among the resin components constituting each of the copolyester layers (B1) and (B2). The main component resin may occupy 50% by mass or more, 70% by mass or more, 80% by mass or more, or, for example, 100% by mass or less of the resin components constituting each of the polyester layers (B1) and (B2).
[0177] When the copolyester (a1) is crystalline, the polyester (B) contained in each polyester layer (B1) and (B2) may be a polyester having a higher melting point than the copolyester (a1). Alternatively, when the copolyester (a1) is amorphous, the polyester (B) is a polyester having a higher melting point than the glass transition temperature of the copolyester (a1).
[0178] In the case of a multilayer structure having a structure in which polyester layers (B1) and (B2) containing polyester (B) as a main component resin are stacked, the raw resin composition is stacked by coextrusion or the like to form polyester layer (B1) / copolyester layer (A1) / polyester layer (B2) and stretched, and then heat-set treatment can be performed at a higher temperature than in the case of a single layer of the copolyester layer (A1). Therefore, the softness can be achieved to a level that cannot be achieved with a single layer of the copolyester layer (A1), or heat shrinkage can be further prevented.
[0179] Specifically, the storage modulus of the copolyester film at 25° C. can be 300 to 2500 MPa, preferably 500 MPa or more, or 2000 MPa or less, and more preferably 800 MPa or more, or 1500 MPa or less.
[0180] In the multilayer structure, the thickness of each of the polyester layers (B1) and (B2) is preferably 1 to 20% of the thickness of the copolyester layer (A1).
[0181] When the thickness of each of the polyester layers (B1) and (B2) is 1% or more of the thickness of the copolyester layer (A1), film formation can be performed without significantly impairing productivity, and when it is 20% or less, required flexibility can be sufficiently ensured, which is preferred.
[0182] From this viewpoint, the thickness of each of the polyester layers (B1) and (B2) is more preferably 3% to 15% of the thickness of the copolyester layer (A1), and particularly more preferably 5% to 12%.
[0183] It should be noted that the thickness of each of the polyester layers (B1) and (B2) present on both the front and back sides of the copolyester layer (A1) may be different or the same on the front and back sides.
[0184] When the copolyester (a1) is crystalline, the polyester (B) is a polyester having a melting point which is preferably 10 to 100°C higher than the melting point of the copolyester (a1), more preferably 20°C or higher, further preferably 40°C or higher, and more preferably 90°C or lower higher, further preferably 70°C or lower higher.
[0185] On the other hand, when the copolyester (a1) is amorphous, the polyester (B) is a polyester having a melting point which is preferably 120 to 260°C higher than the glass transition temperature of the copolyester (a1), more preferably 140°C or higher, further preferably 160°C or higher, and more preferably 230°C or lower higher, and further preferably 200°C or lower higher.
[0186] It should be noted that the polyester (B) as the main component of each of the polyester layers (B1) and (B2) present on both sides of the copolyester layer (A1) may be different or the same on the front and back sides, and it is preferred that the melting points of the polyester (B) on the front and back sides are not significantly different.
[0187] As the polyester (B), for example, a homopolyester or copolyester containing terephthalic acid as a dicarboxylic acid component and ethylene glycol as an alcohol component can be suitably used. However, the present invention is not limited thereto. It should be noted that the homopolyester is polyethylene terephthalate.
[0188] When the polyester (B) is a copolyester, the dicarboxylic acid component other than terephthalic acid includes aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, polyfunctional acids, etc. Examples of these dicarboxylic acid components include the same components as those listed for the copolyester (a1).
[0189] When the polyester (B) is a copolyester, the proportion of the dicarboxylic acid component other than terephthalic acid in the dicarboxylic acid component is preferably 1 to 30 mol%, more preferably 5 mol% or more, more preferably 10 mol% or more, more preferably 25 mol% or less, and even more preferably 20 mol% or less.
[0190] When the polyester (B) is a copolyester, examples of the alcohol component other than ethylene glycol include 1,4-butanediol, 1,6-hexanediol, ethylene glycol, diethylene glycol, trimethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, bisphenol, and derivatives thereof.
[0191] In polyester (B), the proportion of alcohol components other than ethylene glycol in the alcohol components is preferably greater than 1 mol% and less than 100 mol%, more preferably greater than 5 mol%, further preferably greater than 10 mol%, and more preferably less than 95 mol%, further preferably less than 90 mol%.
[0192] <Thickness of the Copolyester Film>
[0193] The thickness of the copolyester film is not particularly limited, and an appropriate thickness can be selected according to the intended use.
[0194] Among them, from the viewpoint of further exerting the characteristics of the copolyester film, the total thickness of the film is preferably more than 5 μm.
[0195] It is said that the hardness of a film is proportional to the cube of its thickness. However, the copolyester film has the following characteristics: even if it has a thickness exceeding 5 μm, its hardness is weak and it is soft, and it is possible to further enjoy the benefits of the present invention.
[0196] From this viewpoint, the total thickness of the copolyester film is preferably more than 5 μm, more preferably 12 μm or more, and even more preferably 30 μm or more.
[0197] The total thickness of the copolyester film is not particularly limited, but is, for example, 200 μm or less, preferably 150 μm or less, and more preferably 100 μm or less.
[0198] (Difference between Tcc and Tg (ΔTcg))
[0199] The difference (ΔTcg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of the copolyester film of the present invention exceeds 60° C. If the difference (ΔTcg) between Tcc and Tg is 60° C. or less, it is difficult to achieve the following opposite characteristics: reduced heat resistance, excellent flexibility, high elongation at room temperature, and good heat resistance.
[0200] From the viewpoint of improving heat resistance, the difference between Tcc and Tg (ΔTcg) is preferably 63° C. or more, more preferably 70° C. or more. The difference between Tcc and Tg (ΔTcg) is not particularly limited, and may be, for example, 150° C. or less, and may be 100° C. or less.
[0201] It should be noted that the cold crystallization temperature (Tcc) is higher than the glass transition temperature (Tg), and the difference between Tcc and Tg (ΔTcg) is defined as "Tcc-Tg".
[0202] The difference between Tcc and Tg can be adjusted by the type and amount of the dicarboxylic acid component (X2), the type and amount of the other alcohol component (Y2), whether or not to stretch, the stretch ratio, the stretch temperature, and the amount of the copolyester (a1).
[0203] The cold crystallization temperature (Tcc) of the copolyester film is not particularly limited, and is, for example, 90 to 150° C., preferably 105 to 135° C. The glass transition temperature (Tg) of the copolyester film is not particularly limited, and is, for example, 10 to 60° C., preferably 25 to 45° C.
[0204] (Tensile elongation at break)
[0205] The tensile elongation at break at 25° C. of the copolyester film is preferably 295% or more. If the tensile elongation at break at 25° C. is 295% or more, the film easily has a high elongation at room temperature and can be properly stretched as described below. In addition, the flexibility of the copolyester film can be ensured.
[0206] In order to ensure flexibility and excellent elongation at room temperature, the tensile elongation at break of the copolyester film at 25°C is more preferably 300% or more, and further preferably 320% or more.
[0207] The tensile elongation at break is not particularly limited, but is, for example, 600% or less, preferably 500% or less, in order to easily impart a certain mechanical strength to the copolyester film.
[0208] (Tensile breaking strength)
[0209] The tensile strength at break of the copolyester film at 25° C. is preferably 30 MPa or more. By setting the tensile strength at break to 30 MPa or more, it is easy to impart a certain mechanical strength to the copolyester film. From this viewpoint, the tensile strength at break at 25° C. is more preferably 40 MPa or more, and further preferably 50 MPa or more.
[0210] From the viewpoint of easily increasing the tensile elongation at break, the tensile strength at break at 25° C. is, for example, 300 MPa or less, preferably 200 MPa or less, more preferably 150 MPa or less, and further preferably 100 MPa or less.
[0211] In the present copolyester film, in order to adjust the tensile elongation at break and the tensile strength at break to the above range, the type and content of the copolymer components of the copolyester (a1) can be adjusted. In addition, it can also be adjusted by whether to stretch, the stretching ratio, etc. Furthermore, it can also be adjusted by the stretching temperature.
[0212] It should be noted that, when MD and TD are known, the tensile elongation at break of the copolyester film is determined by measuring the tensile elongation at break in these directions and adopting the higher value. On the other hand, when MD and TD are unknown, the tensile elongation at break in the direction with the highest tensile elongation at break is adopted. In addition, the tensile strength at break is the value measured in the direction in which the tensile elongation at break is adopted.
[0213] (Storage modulus at 25°C)
[0214] The storage elastic modulus of the polyester film at 25° C. is preferably 2500 MPa or less. By setting the storage elastic modulus at 25° C., i.e., at room temperature, to 2500 MPa or less, flexibility can be ensured, and curved surface conformability can be improved, so that the film can conform to the skin well when a wearable terminal is carried.
[0215] From this viewpoint, the storage elastic modulus at 25° C. of the polyester film is more preferably 2000 MPa or less, particularly preferably 1800 MPa or less, and particularly preferably 1600 MPa or less.
[0216] On the other hand, from the viewpoint of handling properties in each step, the storage elastic modulus at 25° C. is preferably 500 MPa or more, more preferably 800 MPa or more, and even more preferably 1000 MPa.
[0217] In addition, the storage elastic modulus at 25° C. and 120° C. described later is a value obtained by the measurement method described in the examples described later.
[0218] In the present copolyester film, in order to adjust the storage modulus at 25°C to the above range, it can be adjusted by adjusting the type and content of the copolymer components of the copolyester (a1). From this viewpoint, the copolymer components of the copolyester (a1) preferably contain an aliphatic dicarboxylic acid having 4 to 10 carbon atoms, and contain one or both of 1,4-butanediol and 1,6-hexanediol, and the proportion of these in the dicarboxylic acid component and the alcohol component in the polyester (A) is as described above, 3 to 50 mol%, preferably 15 to 60 mol%. The aforementioned aliphatic dicarboxylic acid having 4 to 10 carbon atoms may further preferably be adipic acid.
[0219] Among them, the other alcohol component (Y2) is preferably 1,4-butanediol and 1,6-hexanediol. In this case, the total amount (mol%) of the other alcohol component (Y2) is preferably 15 to 60 mol%.
[0220] The storage modulus at 25°C can also be easily adjusted to the above range by laminating polyester layers (B1) and (B2) containing the polyester (B) as a main component resin on both sides of the copolyester layer (A1) to form a multilayer structure.
[0221] Furthermore, the storage modulus at 25° C. can also be adjusted by the stretching conditions during the production of the copolyester film and the subsequent heat setting conditions.
[0222] (Storage modulus at 120°C)
[0223] The storage modulus of the copolyester film at 120° C. is, for example, 10 MPa or more, preferably 20 MPa or more, particularly 25 MPa or more, and particularly 30 MPa or more.
[0224] It is preferred that the storage elastic modulus at 120°C, that is, near the processing temperature, is 10 MPa or more, particularly 20 MPa or more, because heat resistance is improved. Also, heat shrinkage and the like can be easily suppressed by improving heat resistance.
[0225] The storage elastic modulus at 120° C. is not particularly limited, but is, from the viewpoint of flexibility, for example, 400 MPa or less, preferably 200 MPa or less, and more preferably 150 MPa or less.
[0226] (Crystallization melting enthalpy ΔHm)
[0227] Regarding the copolyester film, when the polyester contained in the copolyester layer (A1) contains a crystalline substance, the crystal melting enthalpy ΔHm of the polyester (when there are two or more polyesters, it is a polyester composition composed of the two or more polyesters) is preferably 15.0 J / g or more, more preferably 20.0 J / g or more, and further preferably 25.0 J / g or more.
[0228] ΔHm is an index of crystallinity, and when it is 15.0 J / g or more, sufficient heat resistance can be obtained, and heat shrinkage of the copolyester film can be suppressed in processing steps including a heat treatment step.
[0229] The crystal melting enthalpy ΔHm is not particularly limited, but is, for example, 50 J / g or less, preferably 40 J / g or less, and more preferably 32 J / g or less, from the viewpoint of flexibility and the like.
[0230] (Young's modulus)
[0231] The Young's modulus of this copolyester film is preferably below 5.0GPa, more preferably below 4.0GPa, and further preferably below 3.5GPa. By setting the Young's modulus to below the above-mentioned upper limit, appropriate flexibility can be ensured. In addition, the Young's modulus is not particularly limited, and is preferably above 0.5GPa, more preferably above 0.8GPa, from the viewpoint of ensuring certain mechanical strength.
[0232] It should be noted that, regarding the Young's modulus of the copolyester film, when MD and TD are known, the Young's modulus in these directions is measured and the higher value is adopted. On the other hand, when MD and TD are unknown, the Young's modulus in the direction with the highest Young's modulus is adopted.
[0233] <Method for producing the copolyester film>
[0234] As an example of the method for producing the copolyester film, a method for producing the copolyester film in the case where the copolyester film is a biaxially stretched film will be described, but the copolyester film is not limited to the method described here.
[0235] First, a raw material, such as polyester chips, is supplied to a melt extruder by a known method, heated to a temperature above the melting point of each polymer, the molten polymer is extruded from a die, and cooled and solidified on a rotating cooling drum to a temperature below the glass transition temperature of the polymer, thereby obtaining an amorphous unoriented sheet.
[0236] Next, the unoriented sheet is stretched in one direction using a roll or tenter stretching machine at a stretching temperature of usually 25 to 120° C., preferably 35 to 100° C., and a stretching ratio of usually 2.5 to 7 times, preferably 2.8 to 6 times.
[0237] Next, the film is stretched in a direction perpendicular to the stretching direction in the first stage. At this time, the stretching temperature is usually 50 to 140° C., and the stretching ratio is usually 3.0 to 7 times, preferably 3.5 to 6 times.
[0238] It should be noted that in the above-mentioned stretching, a method of performing stretching in one direction in two or more stages may be adopted.
[0239] After stretching, the copolyester film can be heat-set at 130 to 270° C. under tension or under relaxation of 30% or less to obtain a biaxially oriented film. The copolyester film can be improved in flexibility, heat resistance, etc. by heat-setting.
[0240] In the case of a single-layer structure of the copolyester layer (A1), the heat setting treatment (also referred to as "heat treatment") is preferably performed at a temperature 5 to 70°C lower than the melting point of the polyester used to form the copolyester layer (A1). In the case of a multilayer structure, the heat setting treatment may be performed at a temperature 5 to 70°C lower than the melting point of the polyester used to form the copolyester layer (A1), and preferably at a temperature 5 to 70°C lower than the melting point of the polyester used to form the polyester layer (B).
[0241] When the copolyester film has a laminated structure of the polyester layer (A1) and the polyester layers (B1) and (B2), the polyester layer (A1) and the polyester layers (B1) and (B2) are coextruded and then stretched and heat-set as a single film as described above.
[0242] <Laminated Film>
[0243] The laminated film according to one embodiment of the present invention comprises the above-mentioned copolyester film and a functional layer provided on at least one surface of the copolyester film. The functional layer is not particularly limited, and a resin layer can be cited. The functional layer such as the resin layer is preferably stretched together with the copolyester film in a state of being laminated on the above-mentioned copolyester film. Thus, the thickness of the functional layer becomes thinner and is formed into a functional sheet.
[0244] The copolyester film is soft and has a higher elongation at room temperature, so it is easy to stretch and is suitable for forming into a functional sheet by stretching. In addition, it has good heat resistance, so even when the laminated film is heated, thermal shrinkage is reduced.
[0245] (resin layer)
[0246] The resin layer is a layer stacked on the copolyester film. The type of the resin layer is not particularly limited, and a resin with stretch-following properties can be suitably used. The resin layer preferably uses a resin layer whose elongation is 295% or more. It should be noted that a resin layer with an elongation of 295% or more means that it does not break even if stretched at an elongation of 295%. In other words, it means that it does not break even if it is stretched at least 295% together with the copolyester film in a state of being stacked on the copolyester film (that is, the stretching ratio is at least 3.0 times). The elongation of the resin layer is more preferably 300% or more, further preferably 350% or more, and particularly preferably 400% or more. The elongation of the resin layer is not particularly limited, and is, for example, 800% or less, preferably 600% or less.
[0247] By satisfying the above range, a thin resin sheet can be stably formed by stretching from a thick state.
[0248] The resin layer may contain ceramic particles in addition to the above-mentioned resin. By using ceramic particles, for example, the stretched resin layer can be used as a green sheet. As the ceramic particles, known ceramic particles used in green sheets can be used. Specifically, barium titanate, Pb(Mg 1 / 3 , Nb 2 / 3 )O3、Pb(Sm 1 / 2 , Nb 1 / 2 )O3、Pb(Zn 1 / 3 , Nb 2 / 3 )O3, PbThO3, PbZrO3, etc., are not particularly limited to them, as long as the dielectric properties required for the ceramic multilayer capacitor can be obtained.
[0249] When the resin layer contains ceramic particles, the resin used includes polyurethane resins, urea resins, melamine resins, water-based polymer-isocyanate resins, epoxy resins, vinyl acetate resins, acrylic resins, etc. In addition, a resin containing a vinyl alcohol structural unit described below can be used.
[0250] When ceramic particles are contained, the ceramic particles may become the main component of the resin layer (eg, 50% by mass or more of the resin layer), and the mass ratio of ceramic particles to resin (ceramic particles) / (resin) is preferably in the range of 70 / 30 to 95 / 5.
[0251] In addition, the resin layer may contain additives such as a dispersant, a plasticizer, an antistatic agent, and a defoaming agent in addition to the resin and the ceramic particles.
[0252] When the resin layer contains ceramic particles in addition to the above resin, it can be formed by applying a slurry containing ceramic particles and resin and dispersing the ceramic particles in any solvent such as water or an organic solvent to the copolyester film, followed by heating and drying.
[0253] In addition, it is also preferred that the resin layer contains a resin as a main component. Here, "containing ... as a main component" means that the content of the resin is preferably 50% by mass or more, preferably 70% by mass or more, preferably 80% by mass or more and 100% by mass or less based on the total amount of the resin layer.
[0254] When a resin is contained as a main component resin, it is preferable to use a resin containing a vinyl alcohol structural unit described later as the resin, and among them, a vinyl alcohol polymer is preferable.
[0255] When the resin layer contains a resin as a main component, it can be formed by diluting a resin composition containing a resin as a main component with an organic solvent, water, etc. as needed, applying it to the copolyester film, and heating, drying, etc. as needed. The resin composition may contain additives such as a crosslinking agent in addition to the resin.
[0256] (Resin containing vinyl alcohol structural unit)
[0257] In the present invention, the resin used in the resin layer is preferably a resin containing a vinyl alcohol structural unit. The vinyl alcohol structural unit is a structural unit formed by -(CH2CHOH)-. Specifically, vinyl acetal polymers such as vinyl alcohol butyral polymers, vinyl alcohol polymers, etc. can be exemplified.
[0258] The vinyl alcohol polymer is obtained by saponifying a polymer obtained by polymerizing a vinyl ester monomer or copolymerizing a vinyl ester monomer and a monomer having an ethylenic double bond other than the vinyl ester monomer.
[0259] In addition, the vinyl alcohol polymer can be unmodified vinyl alcohol, and as mentioned above, a modified vinyl alcohol polymer can be made by using a copolymer with a monomer having an olefinic double bond. In addition, a vinyl acetal polymer can be introduced into a functional group by subsequent reaction. As a modified vinyl alcohol polymer, an acetoacetyl modified vinyl alcohol polymer can be preferably listed.
[0260] The vinyl acetal polymer can be obtained by acetalizing the above-mentioned vinyl alcohol polymer. The vinyl acetal polymer has a hydroxyl group that has not been acetalized, and thus has a vinyl alcohol structural unit. In the case of a vinyl acetal polymer, as the above-mentioned monomer having an olefinic double bond, it is preferred to include a polyfunctional monomer having two or more olefinic double bonds (hereinafter sometimes referred to as a polyfunctional monomer).
[0261] In order to obtain a vinyl alcohol acetal polymer by acetalizing a vinyl alcohol copolymer, the vinyl alcohol copolymer is preferably water-soluble. Therefore, the vinyl alcohol acetal polymer is obtained by, for example, acetalizing a water-soluble vinyl alcohol copolymer containing an olefinic double bond in its side chain. Here, the olefinic double bond in the side chain refers to an unreacted olefinic double bond in a multifunctional monomer copolymerized with the vinyl alcohol polymer.
[0262] When the resin layer contains ceramic particles as a main component, the resin containing the vinyl alcohol structural unit is preferably a vinyl acetal polymer, and particularly preferably a vinyl acetal polymer containing an olefinic double bond in the side chain. By using a vinyl acetal polymer containing an olefinic double bond in the side chain, the dispersibility of the ceramic particles in the slurry is excellent, and the storage stability of the slurry is also improved.
[0263] When the resin layer contains a resin as a main component, a vinyl alcohol polymer is preferably used as the resin containing a vinyl alcohol structural unit. By using a vinyl alcohol polymer, the resin sheet obtained after stretching can be suitably used for optical components such as polarizers.
[0264] Examples of the vinyl ester monomers include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl octanoate, vinyl laurylate, vinyl palmitate, vinyl stearate, and vinyl benzoate. Among these, vinyl acetate is preferred from the viewpoint of easy production.
[0265] Examples of the polyfunctional monomer include monomers containing a vinyl ether group, such as 1,4-butanediol divinyl ether and triethylene glycol divinyl ether; monomers containing an allyl group, such as 1,9-decadiene, polyethylene glycol diallyl ether and pentaerythritol diallyl ether; and monomers having a plurality of (meth)acrylates in one molecule, such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, glycerol tri(meth)acrylate and pentaerythritol tri(meth)acrylate.
[0266] The saponification degree of the vinyl alcohol copolymer is preferably 60 to 99.9 mol%. If the saponification degree is set to 60 mol% or more, the water solubility of the vinyl alcohol copolymer becomes good. From this viewpoint, the saponification degree is more preferably 65 mol% or more. On the other hand, if the saponification degree is set to 99.9 mol% or less, industrial production is easy, and the viscosity stability of the vinyl alcohol copolymer aqueous solution becomes good and easy to handle. From this viewpoint, the saponification degree is more preferably 99.5 mol% or less.
[0267] The viscosity average degree of polymerization Pη of the vinyl alcohol copolymer is preferably 100 to 8000. By setting the viscosity average degree of polymerization Pη to 100 or more, the vinyl alcohol copolymer can be easily produced industrially. From this viewpoint, the viscosity average degree of polymerization Pη is more preferably 200 or more. On the other hand, by setting the viscosity average degree of polymerization Pη to 8000 or less, the vinyl alcohol copolymer can be easily produced industrially. In addition, it is easy to prevent the viscosity of the aqueous solution of the vinyl alcohol copolymer from becoming too high, and its handling becomes easy. From these viewpoints, the viscosity average degree of polymerization Pη of the vinyl alcohol copolymer is more preferably 5000 or less, and further preferably 2500 or less.
[0268] The viscosity average degree of polymerization Pη can be measured in accordance with JIS K6726. Specifically, the vinyl alcohol copolymer is re-saponified to completely saponify the remaining carboxylic acid residues. After the re-saponified vinyl alcohol copolymer is purified and dried, 1 g of the dried sample is added to 100 ml of water, heated and dissolved, and cooled to 30°C. The resulting aqueous solution is measured in a viscometer, and the intrinsic viscosity [η] (unit: L / g) in 30°C water is measured. Based on the measured intrinsic viscosity [η], the following formula (1) is used for calculation.
[0269] [Mathematical formula 1]
[0270] Viscosity average degree of polymerization Pη=([η]×10000 / 8.29) (1 / 0.62 )(1)
[0271] (Adhesive layer)
[0272] The functional layer can be an adhesive layer. By making the functional layer an adhesive layer, the laminated film becomes an adhesive tape. The adhesive layer is a layer with pressure-sensitive adhesive properties, and is formed by a known adhesive. The adhesive is not particularly limited as long as it is a material that can follow the tensile elongation at break even if the copolyester film is stretched to the tensile elongation at break, and existing known materials such as acrylic acid, silicone, urethane, polyester, etc. can be used.
[0273] The adhesive layer may contain a conductive material in the layer. The adhesive layer contains a conductive material to become a conductive adhesive layer (conductive layer) having conductivity. The conductive adhesive layer may be formed of an adhesive compounded with a conductive material.
[0274] As the conductive material, there can be listed metal powder particles such as gold, silver, copper, nickel, and aluminum; conductive carbon particles such as carbon black and graphite; and conductive particles such as resin, solid glass beads, and hollow glass beads having a metal coating on the core surface. As the conductive material, in addition to the conductive particles, conductive polymers can also be used.
[0275] As the conductive material, a conductive polymer can be used. As the conductive polymer, there is no particular limitation as long as it is an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include compounds such as polythiophenes, polypyrroles, polyacetylenes, polyphenylenes, polyphenylene vinylenes, polyanilines, polyacenes, polythiophene vinylenes, and copolymers thereof.
[0276] The conductive material may be used alone or in combination of two or more.
[0277] In addition, the conductive material is preferably at least one selected from carbon black and polythiophenes among the above.
[0278] Polythiophenes are polymers of unsubstituted or substituted thiophene, and specific examples of substituted thiophene polymers include poly(3,4-ethylenedioxythiophene) and the like.
[0279] In addition, the conductive layer is not limited to the conductive adhesive layer, and may be a layer in which a conductive material is blended in a resin layer.
[0280] <Application of the copolyester film>
[0281] As described above, the copolyester film is excellent in flexibility at room temperature, is not only flexible but also has a large elongation and can exhibit sufficient heat resistance for practical use.
[0282] The copolyester film is suitable for various stretching processing applications due to the above properties, and is particularly suitable for stretching molding applications in which various molded products are obtained by stretching.
[0283] In addition, specifically, the copolyester film and the laminated film can be suitably used for battery packaging materials, surface protection films, dicing tapes, adhesive tapes, image display components such as flexible displays, wearable terminals, bioelectrode substrates, biosensor substrates and other bio-related components, electronic component manufacturing purposes, green sheet forming purposes used in, for example, the manufacture of ceramic laminated structures, optical component manufacturing purposes, such as the manufacture of polarizers constituting polarizing plates, etc.
[0284] In addition, among these, it is more preferably used for any of adhesive tape applications, surface protection film applications, semiconductor dicing tape applications, wearable terminal applications, bioelectrode substrate applications, biosensor substrate applications, electronic component manufacturing applications, and optical component manufacturing applications. In particular, it is preferred that a conductive layer containing the aforementioned conductive material is provided on the copolyester film of the present application in the applications of wearable terminals, bioelectrode substrate applications, and biosensor substrate applications.
[0285] Hereinafter, first, the case where the copolyester film is used for stretching processing will be described in more detail.
[0286] The stretching process is not limited as long as it has a process (stretching process) for stretching the copolyester film, and preferably has a process for stretching the laminated film. By stretching the laminated film, the functional layer laminated on the copolyester film is also stretched, so the functional layer can also be stretched. Thus, the functional layer, for example, becomes thinner, and is formed into a functional sheet. The functional sheet can be peeled off from the copolyester film for use as needed.
[0287] In the above-mentioned stretching process, stretching can be performed along a uniaxial direction or a biaxial direction. The stretching ratio is preferably 2.0 to 6.0 times, and more preferably 3.0 to 5.5 times. By setting the stretching ratio within the above-mentioned range, the functional layer and the copolyester film will not have defects, damage, etc., and the thickness can be fully reduced and appropriate stretching processing can be performed. It should be noted that when stretching is performed along a biaxial direction, the stretching ratio refers to the stretching ratio of each axis.
[0288] The stretching can be performed in a dry process or a wet process. The dry process is a process in which the stretching process is performed in the air. The stretching temperature in the dry process is, for example, 25 to 70°C, preferably 30 to 60°C.
[0289] The wet method is a method of stretching a copolyester film or a laminated film immersed in a liquid such as water, and the liquid temperature is, for example, 25 to 70° C., preferably 30 to 60° C. The copolyester film has a high elongation even at near room temperature and can be stretched appropriately.
[0290] As described above, when the functional layer is formed into a functional sheet by stretching, the functional layer may be a resin layer, and may be formed into various resin sheets by stretching. For example, when the resin layer contains resin and ceramic particles, the functional sheet (resin sheet) may be used as a green sheet. The green sheet may be stacked in multiple layers to obtain a ceramic laminated capacitor.
[0291] When the resin layer contains a resin as a main component, the functional sheet can be used as an optical component, and when the resin layer contains, for example, a vinyl alcohol-based polymer as a main component, the functional sheet can be used as a polarizer.
[0292] As described above, the copolyester film can be suitably used for electronic component manufacturing purposes, especially for forming green sheets used in the manufacture of ceramic laminated components, when subjected to stretching processing. In addition, it can also be suitably used for optical component manufacturing purposes, such as the manufacture of polarizers constituting polarizing plates.
[0293] In addition, when the functional layer is an adhesive layer, the laminated film can be used as an adhesive tape. The adhesive tape can be used as long as it is used for household adhesive tape, industrial adhesive tape, packaging adhesive tape, electronic component adhesive tape, etc., and is preferably used for surface protection film purposes, semiconductor dicing tape purposes, etc. The surface protection film is attached to adherends such as electronic components, optical components, and semiconductor wafers to protect the adherends.
[0294] The semiconductor dicing tape is attached to the back of the semiconductor wafer, etc., to support the semiconductor wafer during dicing. In addition, after dicing, the dicing tape is stretched, thereby separating the individual semiconductor chips from each other and allowing them to be picked up.
[0295] The copolyester film has excellent flexibility at low temperatures and a large elongation, so when the adherend to which the adhesive tape is to be pasted has a curved surface or a concave-convex shape, it can follow the adherend and be pasted. Furthermore, when the adhesive tape is used as a dicing tape, it can be easily stretched when picking up semiconductor chips. In addition, it has high heat resistance and is not easy to shrink by heating, so the reliability of the adhesive tape is also improved. For example, when used as a surface protection film, the protective performance becomes good.
[0296] In addition, the copolyester film can be used for bioelectrode substrates, biosensor substrates, etc., and can also be used for bio-related parts such as substrates for wearable terminals. The copolyester film is flexible and has high elongation at low temperatures, so it can easily follow the skin surface and can be suitably used for bio-related parts.
[0297] It should be noted that the bioelectrode substrate and biosensor substrate are substrates that support electrodes or various sensors. Specifically, electrodes and sensor elements can be provided on one surface of the substrate formed by the copolyester film. In addition, the electrode can be composed of a conductive adhesive layer, so an adhesive tape can also be used.
[0298] Furthermore, the copolyester film or laminated film can be used for battery packaging materials such as outer packaging materials for lithium ion batteries, and can also be used for image display components such as flexible displays. Battery packaging materials, image display components, etc. are sometimes bent for use. The copolyester film has flexibility and high elongation at low temperatures, so it can follow the shape of the battery or display and be bent for use. In addition, in these uses, the copolyester film sometimes presents high temperatures, but due to its excellent heat resistance, it can also prevent thermal shrinkage.
[0299] <Description of statement, etc.>
[0300] In the present invention, the term "film" also includes a "sheet", and the term "sheet" also includes a "film".
[0301] In addition, when the term "panel" is used, such as an image display panel, a protective panel, etc., it includes a plate body, a sheet, and a film.
[0302] In the present invention, when "X to Y" (X and Y are arbitrary numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less" as well as "preferably greater than X" or "preferably less than Y".
[0303] In addition, when "X or more" (X is an arbitrary number), unless otherwise specified, it includes the meaning of "preferably greater than X", and when "Y or less" (Y is an arbitrary number), unless otherwise specified, it includes the meaning of "preferably less than Y".
[0304] Example
[0305] Next, the present invention will be described in more detail by way of examples, but the present invention is not limited to the examples described below.
[0306] <Evaluation method>
[0307] Next, the measurement and evaluation of various physical properties were performed as follows.
[0308] (1) Tensile storage modulus E'
[0309] According to JIS K 7244, using a dynamic viscoelasticity measuring apparatus DVA-200 manufactured by IT Measurement & Control Co., Ltd., the polyester film (sample) obtained in the embodiment / comparative example was measured in the width direction (TD) from -100°C to 200°C under the conditions of a vibration frequency of 10 Hz, a strain of 0.1%, and a heating rate of 1°C / min. The tensile storage modulus E' at 25°C and 120°C was obtained from the obtained data as the storage modulus at 25°C and 120°C.
[0310] (2) Crystal melting enthalpy ΔHm
[0311] According to JIS K7141-2 (2006), the differential scanning calorimeter (DSC) measurement of the sample was performed. After the temperature was raised from 30°C to 280°C at 10°C / min, it was kept for 1 minute, then the temperature was lowered from 280°C to 30°C at 10°C / min, it was kept for 1 minute, and then the temperature was raised from 30°C to 280°C again at 10°C / min. At this time, the crystal melting enthalpy (ΔHm) was calculated from the crystal melting peak area during the reheating process.
[0312] In addition, in the case of a single layer, a polyester film was used as a measurement sample, and in the case of a laminated structure, a copolyester layer (A1) was used as a measurement sample.
[0313] (3) Young's modulus
[0314] For the polyester films (samples) obtained in the embodiments and comparative examples, a tensile testing machine (INTESCO MODEL 2001, manufactured by INTESCO) was used to stretch the polyester films (samples) with a length of 300 mm and a width of 20 mm at a deformation rate of 10% / min in a room where the temperature was adjusted to 23°C and the humidity was adjusted to 50% RH. The initial straight line portion of the tensile stress-strain curve was used to calculate the length direction (MD) and width direction (TD) of the film using the following formula.
[0315] E=Δσ / Δε
[0316] (In the above formula, E is Young's modulus (GPa), Δσ is the stress difference based on the initial average cross-sectional area between two points on the straight line (GPa), and Δε is the deformation difference between the same two points / initial length)
[0317] The values were measured at five points each in the longitudinal direction (MD) and the transverse direction (TD) of the film, and the average values were calculated for the respective points.
[0318] (4) Tensile strength
[0319] For the polyester film (sample) obtained in the embodiments / comparative examples, a tensile testing machine (INTESCO MODEL 2001, manufactured by INTESCO) was used. In a room where the temperature was adjusted to 25°C and the humidity was adjusted to 50% RH, a polyester film (sample) with a width of 15 mm was mounted on the testing machine with a chuck spacing of 50 mm, and stretched at a deformation speed of 200 mm / min. The tensile breaking strength in the length direction (MD) and width direction (TD) of the film was calculated using the following formula.
[0320] Tensile strength at break (MPa) = F / A
[0321] In the above formula, F is the load at break (N), A is the initial cross-sectional area of the test piece (mm 2 ).
[0322] The film was measured at 5 points in the longitudinal direction (MD) and the transverse direction (TD), and the average value was calculated for each point.
[0323] (5) Tensile elongation at break
[0324] The polyester films (samples) obtained in Examples and Comparative Examples were subjected to the same test as the above-mentioned tensile breaking strength test, and the tensile breaking elongations in the longitudinal direction (MD) and the transverse direction (TD) of the film were determined by the following formula.
[0325] Tensile elongation at break (%) = 100 × (L-L0) / L0
[0326] Wherein, in the above formula, L is the distance between the marking points at the time of fracture (mm), and L0 is the distance between the initial marking points (mm).
[0327] The film was measured at 5 points in the longitudinal direction (MD) and the transverse direction (TD), and the average value was calculated for each point.
[0328] (6) Heating shrinkage
[0329] The polyester film (sample) obtained in the examples / comparative examples was treated in an oven maintained at 120°C for 5 minutes without tension, the sample lengths before and after were measured, and the heat shrinkage rates in the longitudinal direction (MD) and the width direction (TD) of the film were calculated by the following formula.
[0330] Heating shrinkage (%) = {(L0-L1) / L0}×100
[0331] (In the above formula, L0 is the length of the sample before heating treatment, and L1 is the length of the sample after heating treatment)
[0332] The film was measured at 5 points in the longitudinal direction (MD) and the transverse direction (TD), and the average value was calculated for each point.
[0333] (7) Difference (ΔTcg) between cold crystallization temperature (Tcc) and glass transition temperature (Tg)
[0334] A differential scanning calorimeter (DSC8500 manufactured by Perkin Elmer) was used to read the specific heat change caused by the phase transition from the glass state to the rubber state under the condition of a heating rate of 10°C / min, and Tg (glass transition temperature) was obtained. In addition, the exothermic peak temperature associated with crystallization was taken as the cold crystallization temperature (Tcc). The difference (ΔTcg (°C)) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) was calculated using the following formula.
[0335] ΔTcg=Tcc-Tg
[0336] In the present invention, ΔTcg must be higher than 60° C. The larger the value, the higher the crystallinity.
[0337] In addition, in the case of a single layer, a polyester film was used as a measurement sample, and in the case of a laminated structure, a copolyester layer (A1) was used as a measurement sample.
[0338] (8)Solvent resistance
[0339] After the sample thin film was immersed in each solvent for 24 hours, the state was visually observed and judged according to the following judgment criteria.
[0340] (Judgment Criteria)
[0341] A: No change in appearance or flatness.
[0342] B: The film warps.
[0343] C: Lack of solvent resistance, film dissolved.
[0344] (9) Lamination stretch followability
[0345] A resin layer composition composed of the following components was applied to the sample film and dried at 80°C for 5 minutes to form a functional layer with a thickness of 3.6 μm, thereby preparing a sample composed of a laminated film. Thereafter, the sample was stretched in air at a temperature of 25°C and a stretching ratio of 3.5 times (equivalent to an elongation of 250%) using a tensile testing machine (AUTOGRAPH AG-I) manufactured by Shimadzu Corporation. The stretching followability of the obtained laminated film was determined according to the following criteria.
[0346] (Resin layer composition)
[0347] 100 parts by mass of "GOHSENX Z-200" manufactured by Mitsubishi Chemical Corporation
[0348] 5 parts by mass of "safelink SPM-01" manufactured by Mitsubishi Chemical Corporation
[0349] (Judgment Criteria)
[0350] A: The stretch followability is particularly good.
[0351] B: Good stretch followability.
[0352] C: Poor stretch followability.
[0353] (raw material)
[0354] The following raw materials were used in Examples and Comparative Examples.
[0355] (1) Copolyester (a1-1)
[0356] The following copolyester (a1-1) (intrinsic viscosity (IV) is 0.70 dl / g) is prepared: as dicarboxylic acid components, it contains terephthalic acid and adipic acid (carbon number 6), the content of terephthalic acid is 85 mol%, and the content of adipic acid is 15 mol%; as alcohol components, it contains 45 mol% of 1,4-butanediol and 55 mol% of 1,6-hexanediol.
[0357] (2) Copolyester (a1-2)
[0358] The following copolyester (a1-2) (intrinsic viscosity (IV) is 0.70 dl / g) is prepared: as dicarboxylic acid components, it contains terephthalic acid and isophthalic acid, the content of terephthalic acid is 78 mol%, and the content of isophthalic acid is 22 mol%; as alcohol components, ethylene glycol is 98 mol% and diethylene glycol is 2 mol%.
[0359] (3) Copolyester (a1-3)
[0360] The following copolyester (a1-3) (intrinsic viscosity: 0.64 dl / g) was prepared: as dicarboxylic acid components, it contained terephthalic acid, isophthalic acid and hydrogenated dimer acid having 36 carbon atoms, with terephthalic acid accounting for 88 mol%, isophthalic acid accounting for 5 mol% and hydrogenated dimer acid accounting for 7 mol%; as alcohol components, it contained ethylene glycol accounting for 95 mol% and diethylene glycol accounting for 5 mol%.
[0361] (4) Copolyester (a1-4)
[0362] The following copolyester (a1-3) (intrinsic viscosity: 0.72 dl / g) was prepared: as dicarboxylic acid components, it contained terephthalic acid and hydrogenated dimer acid having 36 carbon atoms, with terephthalic acid accounting for 88 mol% and hydrogenated dimer acid accounting for 12 mol%; as alcohol components, it contained ethylene glycol accounting for 67 mol% and 1,4-butanediol accounting for 33 mol%.
[0363] (5) Copolyester (a1-5)
[0364] A copolyester (a1-5) (with an intrinsic viscosity of 1.6 dl / g) containing terephthalic acid as a dicarboxylic acid component and 1,4-butanediol as an alcohol component was prepared.
[0365] (6) Copolyester (a1-6)
[0366] The following copolyester (a1-6) (intrinsic viscosity: 0.69 dl / g) was prepared: as dicarboxylic acid components, it contained terephthalic acid, isophthalic acid and sebacic acid, with terephthalic acid accounting for 56 mol%, isophthalic acid accounting for 12 mol% and sebacic acid accounting for 32 mol%; as alcohol components, ethylene glycol accounting for 95 mol% and diethylene glycol accounting for 5 mol%.
[0367] (5) Homopolymer polyester (a2-1)
[0368] A homopolyester (a2-1) was prepared: a polyester having a dicarboxylic acid component consisting of terephthalic acid, 98 mol % of ethylene glycol and 2 mol % of diethylene glycol as alcohol components, and having an intrinsic viscosity (IV) of 0.64 dl / g.
[0369] (6) Homopolymer polyester (a2-2)
[0370] A homopolyester (a2-2) was prepared in which the dicarboxylic acid component consisted of terephthalic acid, and as alcohol components, ethylene glycol accounted for 98 mol% and diethylene glycol accounted for 2 mol%, and the intrinsic viscosity (IV) was 0.82 dl / g.
[0371] (7) Homopolymer polyester (a2-3)
[0372] The following particle-containing homopolymer polyester (a2-3) (particle-containing homopolymer PET) is prepared: it is a polyester in which the dicarboxylic acid component is composed of terephthalic acid, and the alcohol components are 98 mol% of ethylene glycol and 2 mol% of diethylene glycol, the intrinsic viscosity (IV) is 0.62 dl / g, and it contains 0.2 mass% of silica particles with an average particle size of 3 μm.
[0373] (8) Homopolymer polyester (a2-4)
[0374] The following particle-containing homopolymer polyester (a2-4) (particle-containing homopolymer PET) is prepared: it is a polyester in which the dicarboxylic acid component is composed of terephthalic acid, and the alcohol components are 98 mol% of ethylene glycol and 2 mol% of diethylene glycol, the intrinsic viscosity (IV) is 0.63 dl / g, and it contains 1.0 mass% of silica particles with an average particle size of 3 μm.
[0375] [Example 1]
[0376] Chips of a polyester composition comprising 50 mass % of copolyester (a1-1), 35 mass % of homopolyester (a2-1) and 15 mass % of homopolyester (a2-3) were fed into a main vented twin-screw extruder set at 270°C.
[0377] The sheet was extruded from a tube head, and solidified by rapid cooling on a cooling roll set at a surface temperature of 25° C. using an electrostatic application method to obtain an unstretched sheet.
[0378] Next, the obtained unstretched sheet was stretched 3.0 times at 75°C in the longitudinal direction (MD) and introduced into a tenter. Then, it was stretched to 4.5 times at 95°C in the width direction (TD) and heat treated at 240°C for 10 seconds to obtain a copolyester film (sample) with a thickness of 50 μm.
[0379] [Example 2]
[0380] Chips of a polyester composition comprising 35 mass % of copolyester (a1-1), 50 mass % of homopolyester (a2-1) and 15 mass % of homopolyester (a2-3) were fed into a main vented twin-screw extruder set at 270°C.
[0381] The sheet was extruded from a tube head, and solidified by rapid cooling on a cooling roll set at a surface temperature of 25° C. using an electrostatic application method to obtain an unstretched sheet.
[0382] Next, the obtained unstretched sheet was stretched 3.0 times at 75°C in the longitudinal direction (MD) and introduced into a tenter. Then, it was stretched to 4.3 times at 95°C in the width direction (TD) and heat treated at 240°C for 10 seconds to obtain a copolyester film (sample) with a thickness of 50 μm.
[0383] [Example 3]
[0384] Chips of a polyester composition comprising 50 mass % of copolyester (a1-1), 20 mass % of homopolyester (a2-2) and 30 mass % of homopolyester (a2-4) were fed into a main vented twin-screw extruder set at 270°C.
[0385] The sheet was extruded from a tube head, and solidified by rapid cooling on a cooling roll set at a surface temperature of 25° C. using an electrostatic application method to obtain an unstretched sheet.
[0386] Next, the obtained unstretched sheet was stretched 3.3 times at 65°C in the longitudinal direction (MD) and introduced into a tenter. Then, it was stretched to 4.7 times at 90°C in the width direction (TD) and heat treated at 230°C for 10 seconds to obtain a copolyester film (sample) with a thickness of 25 μm.
[0387] [Example 4]
[0388] A small piece of a polyester composition containing 25% by mass of copolyester (a1-1), 50% by mass of copolyester (a1-3) and 25% by mass of homopolyester (a2-2) was fed into a main vented twin-screw extruder set at 270° C. The piece was extruded from a tube head, and then quenched and solidified on a cooling roll set at a surface temperature of 25° C. using an electrostatic application method to obtain an unstretched sheet.
[0389] Next, the obtained unstretched sheet was stretched 3.0 times at 90°C in the longitudinal direction (MD) and introduced into a tenter. Then, it was stretched 3.0 times at 90°C in the width direction (TD) and heat treated at 160°C for 15 seconds to obtain a copolyester film (sample) with a thickness of 50 μm.
[0390] [Comparative Example 1]
[0391] Chips of a polyester composition comprising 85% by mass of the copolyester (a1-2) and 15% by mass of the homopolyester (a2-3) were fed into a main vented twin-screw extruder set at 270°C.
[0392] The sheet was extruded from a tube head, and solidified by rapid cooling on a cooling roll set at a surface temperature of 25° C. using an electrostatic application method to obtain an unstretched sheet.
[0393] Next, the obtained unstretched sheet was stretched 3.3 times at 90°C in the longitudinal direction (MD) and introduced into a tenter. Then, it was stretched to 3.7 times at 100°C in the width direction (TD) and heat treated at 190°C for 10 seconds to obtain a copolyester film (sample) with a thickness of 75 μm.
[0394] [Comparative Example 2]
[0395] Chips of a polyester composition comprising 92% by mass of the homopolyester (a2-1) and 8% by mass of the homopolyester (a2-3) were fed into a main vented twin-screw extruder set at 280°C.
[0396] The sheet was extruded from a tube head, and solidified by rapid cooling on a cooling roll set at a surface temperature of 25° C. using an electrostatic application method to obtain an unstretched sheet.
[0397] Next, the obtained unstretched sheet was stretched 3.4 times at 90°C in the longitudinal direction (MD) and introduced into a tenter. Then, it was stretched to 4.5 times at 135°C in the width direction (TD) and heat treated at 223°C for 10 seconds to obtain a polyester film (sample) with a thickness of 50 μm.
[0398] [Comparative Example 3]
[0399] The same operation was carried out as in Comparative Example 2 except that the stretching was not carried out, thereby obtaining an unstretched polyester film (sample) having a thickness of 200 μm.
[0400] [Comparative Example 4]
[0401] As the middle layer, copolyester (a1-4) was fed into a main vented twin screw extruder set at 280°C.
[0402] Separately, as a surface layer, a small piece of a polyester composition comprising 50 mass % of the homopolyester (a2-1) and 50 mass % of the copolyester (a1-2) was fed into a secondary vented twin-screw extruder set at 280°C.
[0403] Co-extrusion is performed in a layer structure of two types of three layers (surface layer / middle layer / surface layer) in such a manner that the polymer from the main extruder becomes the middle layer and the polymer from the secondary extruder becomes the surface layer. The film is extruded from a tube head and solidified by electrostatic application. The film is quenched and solidified on a cooling roller with the surface temperature set to 30°C to obtain an unstretched sheet.
[0404] Next, the obtained unstretched sheet was stretched 3.5 times at 85°C in the longitudinal direction (MD), introduced into a tenter, then stretched to 4.4 times at 100°C in the width direction (TD), and heat treated at 200°C for 10 seconds to obtain a copolyester film (sample) having a thickness of 38 μm. It should be noted that in Table 1, the crystal melting enthalpy ΔHm, the cold crystallization temperature (Tcc), and the glass transition temperature (Tg) are the values of the intermediate layer.
[0405] [Comparative Example 5]
[0406] Chips of a polyester composition comprising 10 mass % of copolyester (a1-1), 30 mass % of copolyester (a1-5) and 60 mass % of copolyester (a1-6) were fed into a main vented twin-screw extruder set at 270°C.
[0407] The film was extruded from a tube head, solidified by electrostatic application, and rapidly cooled on a cooling roll whose surface temperature was set to 25° C. to obtain an unstretched sheet (sample) having a thickness of 200 μm.
[0408] [Reference Examples 1 to 4]
[0409] As reference examples, the following film samples were also evaluated.
[0410] Unstretched PVC: Made by DAIYAPLUS: GR379
[0411] ONY (Stretched Nylon Film): SANTONYL manufactured by Mitsubishi Chemical Corporation
[0412] OPP (oriented polypropylene film): PYLEN P2161 manufactured by Toyobo Co., Ltd.
[0413] CPP (unstretched polypropylene film): Made by DiaPlus: ARTPLY
[0414] [Table 1]
[0415]
[0416] * The mol% of the dicarboxylic acid component and the alcohol component are ratios of the dicarboxylic acid component and the alcohol component, respectively, to the entire polyester (A) contained in the copolyester film (copolyester layer (A1)).
[0417] According to the above-mentioned embodiments and the test results conducted so far by the inventors, for a copolyester film having a copolyester layer (A1) containing a copolyester (a1), wherein the copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X) and an alcohol component (Y2) other than ethylene glycol (Y1), wherein the dicarboxylic acid component (X) comprises a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and the copolyester film comprises two or more other alcohol components (Y2), by making the difference between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) exceed 60°C, the copolyester film has excellent flexibility at room temperature, and not only flexibility but also elongation and strength, and further, sufficient heat resistance for practical use.
[0418] Industrial Applicability
[0419] The copolyester film of the present invention can be used for battery packaging materials, surface protection films, dicing tapes, adhesive tapes, image display components such as flexible displays, wearable terminals, bioelectrode substrates, biosensor substrates and other bio-related components, electronic component manufacturing applications, such as green sheet forming applications used in the manufacture of ceramic laminated components, optical component manufacturing applications, such as the manufacture of polarizers constituting polarizing plates, etc. Among them, it is suitable for applications in which a stretching process is performed in a state of being laminated with different materials, and is particularly suitable for applications having a process of stretching the film by stretching at or near room temperature.
Claims
1. A copolyester film comprising a copolyester layer (A1) containing a copolyester (a1), The copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X2) having 4 to 10 carbon atoms, and an alcohol component (Y2) other than ethylene glycol (Y1). The ratio of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms in the total polyester (A) contained in the copolyester layer (A1) is 3 to 50 mol%. The ratio of the other alcohol component (Y2) in the total polyester (A) contained in the copolyester layer (A1) is 15 to 60 mol%. The difference between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of the copolyester film exceeds 60°C, The other alcohol component (Y2) contains two or more aliphatic diols having 4 to 8 carbon atoms, The total thickness of the copolyester film exceeds 5 μm, The copolyester (a1) accounts for 20% by mass or more of the resin components constituting the copolyester layer (A1).
2. A copolyester film comprising a copolyester layer (A1) containing a copolyester (a1), The copolyester (a1) is a copolymer comprising terephthalic acid (X1), a dicarboxylic acid component (X), and an alcohol component (Y2) other than ethylene glycol (Y1). The other alcohol component (Y2) contains two or more aliphatic diols having 4 to 8 carbon atoms, The ratio of terephthalic acid (X1) in the total polyester (A) contained in the copolyester layer (A1) to the dicarboxylic acid component is 50 to 97 mol%. The ratio of the other alcohol component (Y2) in the total polyester (A) contained in the copolyester layer (A1) is 15 to 60 mol%. The difference between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of the copolyester film exceeds 60°C, The total thickness of the copolyester film exceeds 5 μm, The copolyester (a1) accounts for 20% by mass or more of the resin components constituting the copolyester layer (A1).
3. The copolyester film according to claim 1 or 2, wherein The ratio of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms in the entire polyester (A) contained in the copolyester layer (A1) is 3 to 25 mol % of the dicarboxylic acid components.
4. The copolyester film according to claim 1 or 2, wherein The ratio of the other alcohol component (Y2) in the alcohol components of the entire polyester (A) contained in the copolyester layer (A1) is 15 to 55 mol%.
5. The copolyester film according to claim 1, wherein The dicarboxylic acid component (X2) having 4 to 10 carbon atoms includes adipic acid, The ratio of the dicarboxylic acid component (X2) having 4 to 10 carbon atoms in the entire polyester (A) contained in the copolyester layer (A1) is 3 to 25 mol % of the dicarboxylic acid components.
6. The copolyester film according to claim 1 or 2, wherein The dicarboxylic acid component in all the polyesters (A) contained in the copolyester layer (A1) includes adipic acid, and the ratio of adipic acid in all the polyesters (A) contained in the copolyester layer (A1) to the dicarboxylic acid component is 7 to 40 mol%.
7. The copolyester film according to claim 1 or 2, wherein The ratio of the other alcohol component (Y2) in the alcohol components of the entire polyester (A) contained in the copolyester layer (A1) is 25 to 55 mol%.
8. The copolyester film according to claim 1 or 2, which has a tensile elongation at break at 25°C of 295% or more. 9 . The copolyester film according to claim 1 , which has a storage modulus at 25° C. of 2500 MPa or less and a storage modulus at 120° C. of 10 MPa or more.
10. The copolyester film according to claim 1, wherein The dicarboxylic acid component (X2) having 4 to 10 carbon atoms includes an aliphatic dicarboxylic acid.
11. The copolyester film according to claim 10, wherein The aliphatic dicarboxylic acid includes adipic acid.
12. The copolyester film according to claim 1 or 2, wherein The other alcohol component (Y2) contains 1,4-butanediol.
13. The copolyester film according to claim 1 or 2, wherein: The other alcohol component (Y2) contains 1,4-butanediol and 1,6-hexanediol.
14. The copolyester film according to claim 13, wherein The ratio of the molar amount of 1,6-hexanediol to the molar amount of 1,4-butanediol is 0.5 or more and 1.4 or less.
15. The copolyester film according to claim 1 or 2, wherein: The copolyester layer (A1) further comprises polyester (a2), The polyester (a2) is a polyester other than the copolyester (a1), and contains terephthalic acid as a dicarboxylic acid component and ethylene glycol as an alcohol component.
16. The copolyester film according to claim 1 or 2, wherein: The polyester layer (B1) and the polyester layer (B2) are provided on the front and back sides of the copolyester layer (A1), respectively. 17 . A laminated film comprising the copolyester film according to claim 1 , and a functional layer provided on at least one surface of the copolyester film.
18. The laminated film according to claim 17, wherein The functional layer is a resin layer including a resin containing a vinyl alcohol structural unit.
19. The laminated film according to claim 17 or 18, wherein The functional layer constitutes a green sheet.
20. The laminated film according to claim 17 or 18, wherein The functional layer constitutes a polarizer.
21. The laminated film according to claim 17, wherein The functional layer is an adhesive layer.
22. The laminated film according to claim 21, wherein The adhesive layer includes a conductive material.
23. The laminated film according to claim 17, wherein The functional layer is a conductive layer. 24 . A method for using a copolyester film or a laminated film, comprising the step of stretching the copolyester film according to claim 1 or the laminated film according to claim 17 .
25. The method for using the copolyester film or laminated film according to claim 24, wherein: The stretching is performed in air or in water.
26. The method for using the copolyester film or laminated film according to claim 24 or 25, wherein: The stretching is performed at a stretching ratio of 2.0 to 6.0 times. 27 . The copolyester film according to claim 1 , which is used for any of an adhesive tape, a surface protection film, and a dicing tape for a semiconductor.
28. The laminated film according to claim 17 or 18, which is used for any of an adhesive tape, a surface protection film, and a dicing tape for a semiconductor.
29. The method of use according to claim 24 or 25, wherein: The copolyester film or laminated film is used for any of an adhesive tape, a surface protection film, and a dicing tape for a semiconductor.
30. The copolyester film according to claim 1 or 2, which is used for any of a wearable terminal, a bioelectrode substrate and a biosensor substrate.
31. The laminated film according to claim 17 or 18, which is used for any of a wearable terminal, a bioelectrode substrate, and a biosensor substrate.
32. The method of use according to claim 24 or 25, wherein: The copolyester film or the laminated film is used for any of a wearable terminal, a bioelectrode substrate, and a biosensor substrate.
33. The copolyester film according to claim 1 or 2, which is used for producing electronic parts.
34. The laminated film according to claim 17 or 18, which is used for producing an electronic component.
35. The method of use according to claim 24 or 25, wherein: The copolyester film or laminated film is used for the production of electronic parts.
36. The copolyester film according to claim 1 or 2, which is used for producing an optical member.
37. The laminated film according to claim 17 or 18, which is used for producing an optical member.
38. The method of use according to claim 24 or 25, wherein: The copolyester film or laminated film is used for producing optical components.
Citation Information
Patent Citations
Manufacture of ceramic green sheet
JP1998250014A
Electronic wristwatch
JP2002174688A
Softened polyester film
JP2014169371A
Polyester film for heat-sensitive stencil
JP2019203121A
Copolyester film
TW201920396A